A nursing approach to treat tuberculosis in the Family health strategy (Research, Society and Development, 2021)
Tuberculosis represents a public health problem in Brazil, which is directly associated in most cases with poverty and social exclusion. The present study aimed to carry out an assessment of the Nurse's approach to the treatment of tuberculosis in the Family Health Strategy. This research is a narrative review of the literature. Based on bibliographic research, in the respective databases: Scielo and Virtual Health Library, between the years 2016 to 2020. The Nurse, through the systematized work method, with evaluation of the therapeutic plan, investigation of the patient's life and guidance on the conduct of the treatment, in addition to the valuation of the patient's sociocultural factors, becomes an instrument with great potential, being able to ensure access in the Family Health Strategy and enabling the continuity of tuberculosis treatment. In this way, the nurse in this health-disease process has the necessary attributes to provide care and with total autonomy, as her actions are established in the provision of comprehensive assistance to individuals and families in the Health Strategies of Family, in households and also in community spaces in its area of coverage.